A gender geography of intentional homicide within and outside of the family: male and female murders in Europe, the US and Canada (2003–15) - Minello, A. (European journal of criminology, 2021)
Using the most recent and unpublished international data provided by the United Nations Office on Drugs and Crime, we discuss the geography of male and female homicides in Europe, the US and Canada during the period 2003–15.